2016
DOI: 10.1016/j.atherosclerosis.2016.05.029
|View full text |Cite
|
Sign up to set email alerts
|

TRAF3IP2 mediates atherosclerotic plaque development and vulnerability in ApoE −/− mice

Abstract: Background and aims Atherosclerosis is a major cause of heart attack and stroke. Inflammation plays a critical role in the development of atherosclerosis. Since the cytoplasmic adaptor molecule TRAF3IP2 (TRAF3-Interacting Protein 2) plays a causal role in various autoimmune and inflammatory diseases, we hypothesized that TRAF3IP2 mediates atherosclerotic plaque development. Methods TRAF3IP2/ApoE double knockout (DKO) mice were generated by crossing TRAF3IP2−/− and ApoE−/− mice. ApoE−/− mice served as control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
(56 reference statements)
2
6
0
Order By: Relevance
“…In fact, in a recent study we have observed reduced atherosclerotic plaque burden in female Apoe/TRAF3IP2 double knock-out mice fed a Western diet (52). In another study, TRAF3IP2 was shown to mediate estrogen-deficient osteoporosis (53), further supporting the hypothesis that female sex hormones may negatively regulate TRAF3IP2 expression via mechanisms yet to be investigated.…”
Section: Trafip2 In Adverse Cardiac Remodelingsupporting
confidence: 49%
“…In fact, in a recent study we have observed reduced atherosclerotic plaque burden in female Apoe/TRAF3IP2 double knock-out mice fed a Western diet (52). In another study, TRAF3IP2 was shown to mediate estrogen-deficient osteoporosis (53), further supporting the hypothesis that female sex hormones may negatively regulate TRAF3IP2 expression via mechanisms yet to be investigated.…”
Section: Trafip2 In Adverse Cardiac Remodelingsupporting
confidence: 49%
“…Act1 had been reported to play a vital role in various inflammatory diseases (Pisitkun et al, 2010;Swaidani et al, 2011;Doyle et al, 2012;Wang et al, 2013;Sakamuri et al, 2016). Furthermore, our results indicated Act1 expression in macrophages infiltrated in gingiva and PAPT during periodontitis.…”
Section: Knockdown Of Macrophage-specific Act1 Aggravates Periodontitissupporting
confidence: 63%
“…The macrophages are a key immune cell that regulates the pathophysiology of periodontitis ( Sima et al, 2019 ). Act1 is an intracellular signaling molecule that modulates inflammation in various diseases ( Pisitkun et al, 2010 ; Swaidani et al, 2011 ; Doyle et al, 2012 ; Sakamuri et al, 2016 ). However, the role of macrophage-specific Act1 on the pathophysiology of periodontitis has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Since TRAF3IP2 expression is regulated by multiple oxidative stress‐responsive nuclear transcription factors, including AP‐1, c/EBPβ, and IRF1 (Venkatesan et al, ; Zhao et al, ), it is highly likely that TRAF3IP2 expression is persistently upregulated in vascular inflammatory diseases. Of note, we have previously reported that TRAF3IP2 gene deletion significantly reduces atherosclerotic burden in ApoE –/– mice fed a high fat diet (Sakamuri et al, ).…”
Section: Discussionmentioning
confidence: 88%